O2-S2.02 Sex with stitches, the resumption of sexual activity during the post-circumcision healing period in Zambia. (10th July 2011) - Hewett, P; Mensch, B; Hallett, T; Garnett, G; Dzekedzeke, K; Todd, P
Abstract : Background: As male circumcision (MC) programs are scaled-up for HIV prevention, it is critically important to measure the prevalence of risk behaviours post-MC. Of particular concern is the potential risk of increased HIV-1 transmission and acquisition as a result of premature resumption of sexual activity during the 6-week healing period post-MC, when clients are instructed to abstain from sex. The presentation will review the prevalence of sex post-MC, highlight risk factors for the early resumption of sex and model the impact of such behaviour at the population level. Methods: The study was conducted in four provinces of Zambia in which male circumcision services are being scaled-up. A sample of 248 males aged 15–29 were interviewed via ACASI immediately prior to and 6 weeks after their circumcision; the study follow-up rate was 90%. At baseline, participants were asked about risk behaviours, as well as their knowledge and attitudes about MC. At follow-up, participants were asked about sexual activity in the previous 6 weeks, the timing of resumption of sex post-MC, and other sexual risk behaviours. To evaluate the impact of the study results at the population level, a model was used to estimate the number of new infections that are attributable to the early resumption of sexual activity and the number of infections averted due to the MC program. Results: Preliminary findings indicate that of the men who were followed up, 24% reported resuming sexual activity prior to 6 weeks. The prevalence of early sex is higher (30%) for men who were already sexually active at baseline. Of men who resumed sex prior to 6 weeks, 46% did so in the first 3 weeks post-MC; 22% initiated sex within the first week. Further, 82% reported at least one unprotected sex act, and 26% reported multiple sexual partners. Data also suggest these men had higher risk behaviours at baseline. Modelling the impact of such behaviour indicates that the benefits of the MC program, in terms of HIV infections averted, far out-weigh the costs from the number of new infections generated from the early resumption of sex see Abstract O2-S2.02 table 1 . Conclusion: The resumption of sexual behaviour during the wound healing period poses increased risk for the transmission and acquisition of HIV-1 for individuals. The early resumption of sex is of particular concern for programs that circumcise HIV+ men or a large proportion of men who are not HIV tested. However, at the population level, such behaviour seems less of a concern.